Spatial clustering modifies competition in a diverse annual plant community - Theo L. Gibbs; Zachary J. Gold; Haylee Oyler; Jonathan M. Levine; Nathan J. B. Kraft (Proceedings of the National Academy of Sciences, 2026)
Spatial patterns are widespread in nature, and their formation has been studied extensively. However, the effects of spatial aggregation on the strength of species interactions are less well understood, especially in diverse ecological communities. In a field experiment with annual grassland plants in California, we manipulated the spatial arrangement—but not the number or identity—of two competitors and measured how they jointly affected a focal individual. We found that focal plants produced more seeds when their competitors were clustered than when they were mixed. These results suggest that mixed competitors generally had a more negative effect than clustered competitors. However, the effect of clustering varied across the pairs of competitor species. Competitor species that exhibited greater differences in size and/or functional traits across the spatial arrangements resulted in larger effects of clustering on focal plant seed production. Additionally, a competitive hierarchy among our study species predicted the effects of clustered versus mixed competitors on focal plant seed production. Altogether, our work suggests that the spatial arrangement of competitors changes the realized strength of competition in diverse plant communities. Given the extensive variation in spatial aggregation in plant communities, this mechanism is likely to be a powerful but underappreciated force shaping competition in nature.